Modular Irreducible Representations of the FpW4-Submodules of the Modules as Linear Codes, where W4 is the Weyl Group of Type B4 - F. N. Al-Jobory, Jinan; B. Al-Zangana, Emad; Hassan Ali, Faez (Al-Nahrain Journal of Science, 2021)
The modular representations of the FpWn-Specht modules as linear codes is given in our paper [6], and the modular irreducible representations of the FpW4-submodules of the Specht modules as linear codes where W4 is the Weyl group of type B4 is given in our paper [5]. In this paper we are concerning of finding the linear codes of the representations of the irreducible FpW4-submodules of the FpW4-modules for each pair of partitions of a positive integer n = 4, where Fp = GF(p) is the Galois field (finite field) of order p, and p is a prime number greater than or equal to 3. We will find in this paper a generator matrix of a subspace representing the irreducible FpW4-submodulesof the FpW4-modulesand give the linear code of for each prime number p greater than or equal to 3. Then we will give the linear codes of all the subspaces for all pair of partitions of a positive integer n = 4, and for each prime number p greater than or equal to 3. We mention that some of the ideas of this work in this paper have been influenced by that of Adalbert Kerber and Axel Kohnert [13], even though that their paper is about the symmetric group and this paper is about the Weyl groups of type Bn.